PENGARUH LITERASI, RELIGIUSITAS DAN PERSEPSI TERHADAP MINAT MENABUNG DI BANK SYARIAH (STUDI KASUS MAHASISWA SEKOLAH TINGGI ILMU EKONOMI RIAU) - Diana Sri Dewi; Nurhayana Nurhayana (Jurnal Daya Saing, 2026)
This study aims to determine the effect of Islamic financial literacy, religiosity, and perception on the intention to save in Islamic banks among students of Sekolah Tinggi Ilmu Ekonomi Riau. This research uses a quantitative approach. The population in this study were students of Sekolah Tinggi Ilmu Ekonomi Riau, with an unknown total population. The sample consisted of 115 respondents, determined based on Hair et al.’s recommendation by multiplying 23 statement items by 5. The sampling technique used was purposive sampling. Data were collected through questionnaires and analyzed using instrument testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results showed that Islamic financial literacy has a positive and significant effect on the intention to save in Islamic banks, with a t-count value of 2.168 > t-table 1.981 and a significance value of 0.032 < 0.05. Religiosity has a positive and significant effect, with a t-count value of 3.257 > 1.981 and a significance value of 0.001 < 0.05. Perception also has a positive and significant effect, with a t-count value of 12.834 > 1.981 and a significance value of 0.001 < 0.05. Simultaneously, Islamic financial literacy, religiosity, and perception have a significant effect on the intention to save in Islamic banks, with an F-count value of 243.101 > F-table 2.69 and a significance value < 0.05.